The Mother Country and Her Colonial Progeny - L. Falconer (Law Text Culture, 2003)
The ideological space created by the British Empire provided opportunities for explorations into the meanings of Victorian femininity. Woman could be the intrepid missionary, bringing light to dark Africa; the memsahib creating conflict in the colonies with her petty jealousies; or a vulnerable piece of her husband’s property to be defended from the ‘other’. She could also be the heroic mother responsible for the preservation of the race, or, simply an object of intensifying legal control over her reproductive capacities.